Incidence and detection of seed mycoflora of Indian mustard (Brassica juncea L) and their deteriorative effect on plant health (Journal of Oilseed Brassica, 2026)
Sixteen saprophytic as well as parasitic mycoflora belonging to eight genera were recorded in the blotter and agar plate methods. These were Alternaria brassicae, A. alternata, A. brassicicola, Aspergillus niger, A. flavus, A. nidulans, A. fumigatus, A. ochraceous, Curvularia lunata, Drechslera tetramera, Rhizopus nigricans, Mucor sp., Penicillum sp., Chaetomium sp., Metarrhizium sp. and Fusarium oxysporum. The fungal species recorded in potato dextrose agar plate method (PDA) test were common to those observed in blotter test but percent incidence of fungi varied in blotter test and PDA. Sample collected from Alwar showed maximum incidence of mycoflora. Six fungal species belonging to four genera including A. brassicae were found pathogenic and adversely affect plant status. A. brassicae was found to be highly pathogenic as it showed maximum reduction in seed germination and vigour index with enhanced pre and postemergence mortality and produced symptomatic seedling with small necrotic lesions on cotyledonary leaves. Pathogenic seed mycoflora including A. brassicae were recovered maximum on seed coat followed by endosperm while absent on cotyledon and embryo.